2019
DOI: 10.3390/medicina55080493
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Carbamylated LDL and Soluble Lectin-Like Oxidized Low-Density Lipoprotein Receptor-1 Are Associated with Coronary Artery Disease in Patients with Metabolic Syndrome

Abstract: Background and objectives: Lectin-like oxidized low density lipoprotein receptor-1 (LOX-1) has been recognized as the primary receptor for carbamylated low-density lipoproteins (cLDL) and is increasingly being viewed as a critical mediator of vascular inflammation and atherosclerosis. The aim of the current study was to evaluate the possible role of circulating cLDL and soluble LOX-1 (sLOX-1) as potential biomarkers of metabolic syndrome (MetS) as well as of coronary artery disease (CAD) among MetS patients. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 52 publications
(87 reference statements)
0
7
0
Order By: Relevance
“…Recently, LOX-1 is being viewed as a critical mediator of atherosclerosis and vascular inflammation. Elevated serum levels of soluble LOX-1, a fragment of the main LOX-1 molecule, have been evaluated as promising biomarkers for diagnosis and risk assessment of metabolic syndrome and coronary artery disease among the metabolic syndrome population [7].The present study on arthritis has demonstrated the roles…”
Section: Introductionmentioning
confidence: 70%
“…Recently, LOX-1 is being viewed as a critical mediator of atherosclerosis and vascular inflammation. Elevated serum levels of soluble LOX-1, a fragment of the main LOX-1 molecule, have been evaluated as promising biomarkers for diagnosis and risk assessment of metabolic syndrome and coronary artery disease among the metabolic syndrome population [7].The present study on arthritis has demonstrated the roles…”
Section: Introductionmentioning
confidence: 70%
“…However, we could not confirm a potential elevation of sLOX-1 in our patients because we did not measure sLOX-1 levels in healthy control subjects. Notably, recent studies have shown significantly higher circulating sLOX-1 levels in patients with single-, double-, and multiple-vessel coronary artery disease (CAD) 43 or in those with CAD complicated by metabolic syndrome, 44 compared to healthy subjects. In addition, baseline sLOX-1 concentrations have been found to be correlated with major adverse cardiovascular events (MACE) in patients with stable CAD, 45 and there may be a further increase of sLOX-1 in situations of ulcerated plaques.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was confirmed in a study using oral administration of urea to Apoe -/mice leading to an eight-fold increase in blood cLDL levels and more severe progression of atherosclerosis than in control mice [190] . Due to myeloperoxidase, there is an alternative mechanism in which thiocyanate is oxidized in the presence of H 2 O 2 to cyanate in smokers [191,192] .…”
Section: Mechanism Of Ldl Carbamylationmentioning
confidence: 99%